2009
DOI: 10.1186/1743-422x-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus p37 interacts with host proteins associated with LE-derived transport vesicle biogenesis

Abstract: Background: Proteins associated with the late endosome (LE) appear to play a central role in the envelopment of a number of taxonomically diverse viruses. How viral proteins interact with LEassociated proteins to facilitate envelopment is not well understood. LE-derived transport vesicles form through the interaction of Rab9 GTPase with cargo proteins, and TIP47, a Rab9-specific effector protein. Vaccinia virus (VV) induces a wrapping complex derived from intracellular host membranes to envelope intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Although Retro-2 did not interfere with palmitoylation, it was of interest to determine the effect of the drug on F13 localization. Previous studies had shown that F13 associates with early and late endosomes in addition to the TGN (59,60). Cells were transfected with cytomegalovirus (CMV) vectors expressing TGNP, Rab7, or Rab5 fused to fluorescent tags in order to localize the TGN, late endosomes, and early endosomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although Retro-2 did not interfere with palmitoylation, it was of interest to determine the effect of the drug on F13 localization. Previous studies had shown that F13 associates with early and late endosomes in addition to the TGN (59,60). Cells were transfected with cytomegalovirus (CMV) vectors expressing TGNP, Rab7, or Rab5 fused to fluorescent tags in order to localize the TGN, late endosomes, and early endosomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Data from these time points confirmed that the fusion protein accumulated in the same fractions as reported previously. Several wellstudied plant and animal viruses have been shown to relocate host proteins by altering signals on endomembranes (7,11,32,34,36). It is possible that CHV1 factors present in the vesicles alter their original destination.…”
Section: Figmentioning
confidence: 99%
“…Because TIP47 is also involved in lipid droplet biogenesis under conditions of rapid fat storage, it remains to be determined if TIP47 might be a shared effector that also interacts with one of the myriad of Rab GTPases involved in lipid droplet formation or, alternatively, promotes interorganellar tethering to lipid droplets to allow access to critical lipid regulators of endocytosis Bulankina et al 2009;Hynson et al 2012). Indeed, Tip47 and Rab9 are important targets in viral infectivity and have been associated with lipid droplet consumption, suggesting that resolving this open question will be of significant interest (Murray et al 2005;Chen et al 2009b;Carvalho et al 2012;Vogt et al 2013). Based on the cumulative evidence, it is speculated that Rab-mediated cargo selection and vesicle budding will involve specific lipid recruitment through cis or trans membrane interactions, signal-dependent cargo binding, cooperativity between Arf and Rab GTPases, and GTPase regulatory factors for spatiotemporal control of protein -protein interactions.…”
Section: Rab Gtpases In Vesicle Buddingmentioning
confidence: 99%